Application status of continuing nursing care model in the Traditional Chinese Medicine nursing clinic (延续护理模式在中医护理门诊中的应用现状) - LI Xu (李旭); ZHANG Lili (张莉莉); JI Yunfei (吉云飞); LI Mingzhu (李明珠) (Association of Integrative Nursing, 2022)
This paper summarized the development status and development mode of Traditional Chinese Medicine(TCM) nursing clinic, introduced the connotation and development status of continuous nursing, and discusses the practical significance and implementation form of applying continuing nursing to TCM nursing clinic, so as to provide some reference for the further construction and development of TCM nursing clinic. (本文对中医护理门诊的发展现状及开展模式进行综述, 介绍延续护理的内涵与发展现状, 探讨将延续护理应用于中医护理门诊的现实意义和实施形式, 以期为中医护理门诊进一步建设和发展提供一定借鉴与参考。)